2019
DOI: 10.1111/jch.13581
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal on‐treatment diastolic blood pressure range using automated measurements in subjects with cardiovascular disease—Analysis of a SPRINT trial subpopulation

Abstract: Automated office blood pressure measurement (AOBPM) is recommended for diagnosing hypertension; however, optimal treatment targets using this method are not established. Discrepancies between automated and office measurements of blood pressure have been described, producing uncertainty regarding the use of AOBPM in clinical practice. The Systolic Blood Pressure Intervention Trial (SPRINT) results improved our understanding of target AOBPM systolic blood pressure (SBP) levels; however, diastolic blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In the first approach (10 mm Hg-wide optimal DBP range), in accordance with the current ESC guidelines, the optimal on-treatment DBP range should be 10 mm Hg wide. Such approach was successfully applied previously in the group of SPRINT participants with CVD [10].…”
Section: Selecting the Optimal On-treatment Dbp Rangementioning
confidence: 99%
See 1 more Smart Citation
“…In the first approach (10 mm Hg-wide optimal DBP range), in accordance with the current ESC guidelines, the optimal on-treatment DBP range should be 10 mm Hg wide. Such approach was successfully applied previously in the group of SPRINT participants with CVD [10].…”
Section: Selecting the Optimal On-treatment Dbp Rangementioning
confidence: 99%
“…The European Society of Cardiology recommended the target DBP range of 70-79 mm Hg for all patients; however, more studies are warranted to evaluate this issue [6]. Using the SPRINT data, we previously reported that in the subpopulation with CVD, the optimal DBP using AOBPM ranged between 68.6 and 78.6 mm Hg [10]. Both elevated and extremely low on-treatment DBP values were associated with unfavourable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of this analysis was similar to the primary composite cardiovascular outcome of main SPRINT analysis. By applying hazard ratio plots with cubic spline regression, the analysis showed a U‐shaped relationship between achieved diastolic BP and the risk for the composite cardiovascular outcome . Participants with achieved diastolic BP ranging from 68.6 to 78.6 mm Hg appeared to carry the lowest risk for the composite cardiovascular outcome.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Clinical Hypertension , Sobieraj et al report a non‐prespecified, post hoc analysis of 1470 SPRINT participants with prior cardiovascular disease aiming to explore the association of achieved diastolic BP with clinical outcomes. The predictor in this analysis was defined as the mean on‐treatment (achieved) diastolic BP from the follow‐up visit at 6 months till the trial completion.…”
mentioning
confidence: 99%
See 1 more Smart Citation